2018
DOI: 10.1016/j.ejphar.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

DSP-6952, a novel 5-HT 4 receptor partial agonist, inhibits visceral hypersensitivity and ameliorates gastrointestinal dysfunction in experimental animals

Abstract: The pharmacological profile of DSP-6952, a novel 5-HT receptor partial agonist, was investigated to evaluate the potential use for GI disorders, and to compare its effects in some GI dysfunction models with those of clinically efficacious prokinetic agents. DSP-6952 enhanced gastric motility and caused colonic giant migrating contractions (GMCs) associated with defecation in conscious dogs, having ED value for inducing GMCs of 1.56 mg/kg. DSP-6952 (3-10 mg/kg, i.g.) significantly enhanced colonic transit rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The affinity for the 5‐HT 4 receptors is almost comparable to that in prucalopride 16 . Minesapride has potent enterokinetic effects and shows minimal effects on human Ether‐a‐go‐go related gene potassium channels in pre‐clinical studies 16,17 . In clinical studies, a phase 1 (first in human) study showed minesapride exposure in plasma increased in a dose‐proportional manner with acceptable safety profile up to 120 mg/d 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The affinity for the 5‐HT 4 receptors is almost comparable to that in prucalopride 16 . Minesapride has potent enterokinetic effects and shows minimal effects on human Ether‐a‐go‐go related gene potassium channels in pre‐clinical studies 16,17 . In clinical studies, a phase 1 (first in human) study showed minesapride exposure in plasma increased in a dose‐proportional manner with acceptable safety profile up to 120 mg/d 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several opioid, cannabinoid, and 5-HT receptors play critical roles in visceral hypersensitivity and abnormal gut motility associated with IBS and also contribute to the maladaptive effects of chronic morphine analgesia including hyperalgesia, tolerance, and dependence [29][30][31]. Therefore, we speculate that the visceral hyperalgesia induced by MAM modeling may be mediated by interactions between microorganisms and their host receptors.…”
Section: Discussionmentioning
confidence: 94%
“…In studies with non-clinical endpoints, minesapride enhanced gastrointestinal motility and colonic transit and inhibited visceral hypersensitivity. 6 These results suggested possible efficacy in IBS-C. As for cardiovascular risks, unlike tegaserod, minesapride has negligible binding affinities for the 5-hydroxytryptamine (5-HT) 1B/1D or other receptors presumably involved in vasoconstriction. Moreover, minesapride showed no contractile response on isolated coronary arteries.…”
Section: N V I T E D E D I T O R I a L Editorial: Minesapride For Imentioning
confidence: 92%